2004
DOI: 10.1121/1.1772400
|View full text |Cite
|
Sign up to set email alerts
|

Improved algorithms and methods for room sound-field prediction by acoustical radiosity in arbitrary polyhedral rooms

Abstract: This paper explores acoustical (or time-dependent) radiosity--a geometrical-acoustics sound-field prediction method that assumes diffuse surface reflection. The literature of acoustical radiosity is briefly reviewed and the advantages and disadvantages of the method are discussed. A discrete form of the integral equation that results from meshing the enclosure boundaries into patches is presented and used in a discrete-time algorithm. Furthermore, an averaging technique is used to reduce computational requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Alternative geometries commonly seen in single volume halls, such as fan-shape and vineyard styles, could also be studied. Different modeling methods, such as physical scale modeling, radiative transfer models, 32,33 diffusion models, 34,35 and finite difference time-domain methods, 36 could be used to make additional conclusions about the influence of architectural parameters on DSE and its subjective impression. Aspects of the subjective response to DSE could be further investigated as well.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative geometries commonly seen in single volume halls, such as fan-shape and vineyard styles, could also be studied. Different modeling methods, such as physical scale modeling, radiative transfer models, 32,33 diffusion models, 34,35 and finite difference time-domain methods, 36 could be used to make additional conclusions about the influence of architectural parameters on DSE and its subjective impression. Aspects of the subjective response to DSE could be further investigated as well.…”
Section: Discussionmentioning
confidence: 99%
“…59 The basic principle of presenting such reflection characteristics is the same as that of the above-mentioned BRDF model, but it is called the reflection matrix. The diffuse reflection variant of the equation was further refined by Nosal et al 60 to contain a source term that enables the computation of timeenergy responses, whereas the previous versions were only used to study the energy balance in the room.…”
Section: Model Of Geometrical Room Acoustics-room Acoustic Renderimentioning
confidence: 99%
“…158 A major step in acoustic radiosity was taken in 2004 when Nosal et al presented, in detail, how the technique can be used to predict the sound field in non-rectangular rooms with ideally diffusely reflecting boundaries. 60 The paper also includes validation against analytical solutions in a spherical enclosure. The algorithm computes the radiation density, which is also known as the radiance in later papers, and follows the same iterative propagation principle, as illustrated in Fig.…”
Section: A Radiositymentioning
confidence: 99%
“…The ray tracing method [1,2], the image source method [3,4], beam tracing [5] and acoustic radiosity [6,7] are some of these methods. One review of them can be found in [8].…”
Section: Introductionmentioning
confidence: 99%